Optimal strawberry distribution in Mexico (cycle 2023): a linear programming model - Grajales-Hernández, Omar; Flores-González, Pablo Iván; Núñez-Betancourt, Ernest Yasser; Gómez-Gómez, Alma Alicia; Luquez-Gaitan, Carlos Ernesto (Revista Mexicana de Ciencias Agrícolas, 2026)
Strawberries are a strategic crop in Mexico due to their economic and social importance, with more than 640 000 t produced in 2023, concentrated in Michoacán, Guanajuato, and Baja California. Their high perishability requires efficient logistics systems. The study aimed to estimate the optimal strawberry distribution routes for the 2023 cycle, using a linear programming model that minimizes the total distance transported, comparing closed- and open-economy scenarios. To do this, linear programming was applied using the simplex method in Lingo 18.0, considering distance as a cost variable. In the first scenario (closed economy), 4 of the 16 producers concentrated 95% of the supply and supplied the 28 demanding destinations; in the second (open economy), a surplus of 158 000 t was exported, mainly via Mexicali, Tijuana, and Matamoros. The model allowed us to minimize the variable of travel distance; however, limitations were identified, such as the absence of monetary costs, seasonality and a lack of storage infrastructure. In conclusion, strengthening these areas will increase the competitiveness of the strawberry sector and improve national food security.